Role of Non-Steroidal Anti-Inflammatory Drugs in Gynecology - Anna Livshits; Daniel S. Seidman (MDPI AG, 2010)
This review summarizes the current use of non-steroidal anti-inflammatory drugs (NSAIDs) in obstetrics, gynecology and infertility. These medications are commonly used in different fields of reproductive medicine, for pain management after operative procedures and to relieve dysmenorrhea. In addition to their analgesic effect, NSAIDs are helpful in the management of menorrhagia by decreasing menstrual blood loss. NSAIDs alleviate pain associated with medical abortion, assist in undertaking natural cycle in-vitro fertilization by preventing follicular rupture and reducing premature ovulation, and serve as tocolytics in preterm labor. New NSAIDs may have a growing role in management of women's health.